Investigating the role of transformation leadership on Public sector employee’s job satisfaction during Covid-19: The mediating role of employee Empowerment - BHATTI, QAISSR ABBAS; AHMAD, MUNAWER JAVED; AKRAM, MUHAMMAD; AHMAD, RIAZ (The journal of contemporary issues in business and government, 2021)
The global economy is suffering as a result of the Covid-19 pandemic. Because of the health and psychosocial issues, both private and public sector organizations are impacted. Leaders and employees must be committed, engaged, and supportive during this crucial process. To ensure that the overall process runs smoothly, leaders should act and energize on the same page and same attitudes, i.e., transformational leadership styles. Hence, this study attempted to examine the effect of transformational leadership on employee satisfaction during Covid-19, along with the mediating role of employee empowerment between the transformational leadership and employee satisfaction of employees working in public sector organizations. The results of this study revealed the positive association between characteristics of transformational leadership such as coping with uncertainty and ambiguity, guidance and support, risk management, and supporting teamwork, with job satisfaction. Moreover, the mediating results of this study show that employee empowerment significantly mediates the relationship between coping with uncertainty and ambiguity, guidance and support, risk management, and job satisfaction. The current study validates that the characteristics of transformational leadership have a strong effect on job satisfaction among public sector employees. Therefore, the role of transformational leaders during increased healthcare and psychosocial challenges is highly influential. The limitations and future recommendations are also conveyed in this study.